Влияние оксиэтилированного глицерина со степенью полимеризации n = 5 на термостабильность гемоглобина человека - Zinchenko, Aleksandra V.; Govorova, Yulianna S.; Kompaniets, Antonina M. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2013)
The effect of oxyethylated derivative of glycerol with polymerization degree n = 5 (OEGn=5) on thermodynamic and kinetic parameters of hemoglobin melting was studied by the method of differential adiabatic scanning microcalorimetry. It was shown that increase of OEGn=5 concentration in solution resulted in reduction of the temperature and calorimetric enthalpy of hemoglobin thermodenaturation. It was suggested that the increasing of cryoprotective concentration induced the loosening of hemoglobin molecules thereby contributing to the reduction of thermal stability of protein. The possibility of using kinetic approach when analyzing hemoglobin melting process was shown.